The knowledge, perceptions and relationship behaviour of rugby and football players towards HIV infection at the University of Limpopo - Indiran Govender; Kathryn Nel; Nhlanhla Banyini (AOSIS, 2018)
Background: Sport has the capability to unite a country. To achieve winning teams, athletes have to rely on each other and often have close physical contact. Disclosure of a positive human immunodeficiency virus (HIV) status may be problematic for athletes in contact sports as they may suffer discrimination and stigmatisation which may impact their relationship behaviours. This may impact frontline nursing and medical staff dealing with on-field 'blood' injuries. Objectives: The purpose of this study was to determine if individuals who participate in football and rugby are aware of the risk of HIV infection in contact sports and their perceptions and reported behaviour towards HIV-positive athletes. Method: A cross-sectional survey design with a qualitative element. Quantitative data were analysed using descriptive statistics, while thematic content analysis was used to analyse qualitative data. Non-proportional quota sampling was used for male rugby (n = 23) and football (30) players registered at the University of Limpopo (Turfloop campus). Results: The results supported previous research in that there are gaps in HIV knowledge. For instance, not knowing that anal sex may cause HIV infection and believing that saliva can transmit HIV and that blood transfusions are unsafe. Conclusion: Problematic findings were that a portion of the sample believed that having sex with a virgin could cure HIV and the majority of the sample believed that being 'bewitched' could cause HIV and acquired immunodeficiency syndrome (AIDS).